Participation in export and Chinese firms' capacity utilization. Issue 5 (3rd July 2016) - Tian, Xian-Liang
Abstract : This paper first sets up a firm heterogeneity trade model and shows that given capital stock and productivity, export firms will have higher rates of capacity utilization. In addition, given capital stock and fixed export costs, firms with higher productivity are more likely to export. I then use the 2012 Chinese enterprise survey from the World Bank to empirically investigate the impact of participation in export on Chinese firms' capacity utilization rate. The results show that on average, export firms have capacity utilization rate 1.55–2.01 percent higher than non-export firms, which amounts to 14.6–18.9 percent of the standard deviation of capacity utilization rate in the sample. I also find that firms with a larger part of shares owned by the government have lower capacity utilization. Stronger market competition leads to over-investment and therefore lower capacity utilization rate. Faced with more rigorous labor market regulation, firms will substitute capital for the use of labor, resulting in higher capacity utilization rate.